Program Santri Wirausaha Melalui Pelatihan Pengolahan Bakso Ikan Patin (Pangasius sp.) - Rita Khairina; S. Nooryantini; Albar Hidayat; Sri Dewi N. Sitorus (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Wali Songo Islamic Boarding School, Guntung Manggis Village, Kecamatan Ulin Banjarbaru, is one of the pesantren of 14 Islamic boarding schools in Banjarbaru City. The problem that was found was that while studying at the Islamic boarding school, the students were only given religious lessons and the students were not equipped with community empowerment-based knowledge and skills so that after graduating the students had economically-oriented skills independently in the community. The solution offered is training in the processing of catfish meatballs, which is a simple, easy, inexpensive, and economical skill technology if managed and carried out seriously. The target outcome plan is the success of the santri entrepreneurship program and scientific publications in the Jati Emas community service journal. Participants were 25 people consisting of 20 santri and 5 ustadzah. All participants were divided into 5 groups, each group consisting of 4 students and 1 ustazdah. Each group was given the opportunity to process fish balls from handling fish to turning them into meatballs. Participant participation was very high, as seen from the very dynamic activities of each group. All equipment used during the training was handed over to the boarding school as a motivation for them to have business capital in the form of equipment. At the end of the meeting the leadership of the boarding school stated that they would provide direction to the students to start processing fish balls for consumption needs at the boarding school and then they could be used as an economic business for the Wali Songo Islamic Boarding School.